Model Pembelajaran Problem Based-Learning (PBL) dan Media Powerpoint: Teknik dan Strategi Guru Sebagai Agen Pembelajaran dalam Meningkatkan Minat Belajar Peserta Didik - Susi Susanti (JURNAL BANUA OGE TADULAKO, 2021)
Problem Based-Learning (PBL) is often contrasted with the conventional learning and to modified technical and strategic of learning based-on problem in the classroom. Since it used to discovery and modified learning routine educators or teacher in the past ten years (Cifti, 2015; Nur Jannah, 2014; Ananth & Rusiyanto, 2012; Susanti, E., Ritonga, M., & Bambang, B., 2020; Minardi, J., & Akbar, A. S., 2020). Research by Susanti, E., Ritonga, M., & Bambang, B., 2020; Minardi, J., & Akbar, A. S., 2020 stated that the Problem Based-Learning is significantly and good proof able to increase the attention and the interest of student in active learning. However, the use of Problem Based-Learning by the teacher as a learning agent becomes ineffective if the student were not interested in the problems to be solved in the class. Therefore, it takes strategic and technical of learning by the role of instructional media to stimulate student interest. The Technical and strategic use media which could be integrated in learning media above, Power Point is selected and issued could to increase, motivate, support the model of Problem Based-Learning (PBL). Problem Based-Learning (PBL) is learning of media can appropriate media to focus and alternative media to address these issues.